Endocrine therapy for prostate cancer: review of the latest clinical evidence. (April 2011) - Tsao, Che-Kai; Seng, Sonia; Oh, William K; Galsky, Matthew D
Prostate cancer, the most common nonskin cancer in men, is estimated to cause 27, 000 deaths annually in the USA. With the advent of prostate-specific antigen screening, most are diagnosed with local disease, but approximately one-third of patients ultimately develop recurrence despite definitive local therapy. Despite the high initial response rate to androgen deprivation, castration resistance eventually develops. In this article, we examine mechanisms of androgen resistance and further discuss current progress in the development of novel endocrine therapy in the treatment of castration-resistant prostate cancer. We also explore the rationale of complete androgen blockade, with current ongoing investigation of combination hormonal therapy in this context.